Adsorption of Methylene Blue Dye from Aqueous Solution Using Activated Cogon Grass (Imperata cylindrica) Fixed on Alginate - Eden S. Erasga; Angelica R. Matienzo; Allyssa Joy N. Nanola; Alexander Jimuel B. Vibar (Chemical Engineering Transactions)
The continuous discharge of large volumes of colored effluents into water bodies has been contributing to environmental problems over the years. Extensive research has been conducted, over time, to investigate various treatment methods for effectively removing methylene blue (MB) dye from textile wastewater. In this study, activated cogon grass-alginate beads (ACAB) were successfully prepared by fixing the activated cogon grass in an alginate matrix using dropwise extrusion in calcium chloride solution. The adsorbent before and after adsorption was characterized using Energy Dispersive X-ray Spectroscopy (EDX) for elemental percentages, Fourier Transform Infrared Spectroscopy (FTIR) for functional groups, and Scanning Electron Microscope (SEM) for surface morphology. Batch adsorption experiments were carried out to determine the effect of increasing adsorbent dosage and effect of increasing pH on the adsorption of MB on ACAB. The findings showed that the highest color removal efficiency reached 96.34 %, resulting in a final total color units (TCU) concentration of 4.09 ppm and an adsorption capacity of 6.02 mg/g (at 8 % adsorbent dosage, pH 8.0, agitation at 300 rpm and contact time of 1 h). The MB adsorption process on ACAB adhered to the Flory-Huggins isotherm and demonstrated a good fit with a pseudo-second-order model. The inherent spontaneity of this adsorption phenomenon, coupled with an increasing degree of disorder, was verified through the analysis of thermodynamic parameters. Specifically, the values of ?G (-4.62 kJ/mol) and ?S (+15.48 J/K·mol) provided compelling evidence for the thermodynamic favorability and the associated rise in entropy during the process.